The Impact of Intimate Partner Violence on Women in Criminal Courts: Beyond the Victim-Survivor Dichotomy - Aizpitarte, Alazne (Victims & offenders, 2024)
The experience of violence directly impacts abused women’s sense of self. This study explores the identity construction processes of women who have experienced intimate partner violence. It mainly focuses on analyzing how being involved in violent relationships and going through the criminal justice system has impacted women’s self-perception. The participants were twenty-three women residing in Spain (aged 23–65) whose cases had been reported and prosecuted. In-depth interviews were conducted to collect their experiences based on a phenomenological qualitative research methodology. Results showed that the victim-survivor dichotomy does not enable us to capture the diversity and complexity of women’s experiences. The construction of their identity is, to a large extent, influenced by the psychological impact of the criminal process. The expectations derived from the stereotyped conception of the ideal victim and the ambivalent messages they receive from various social agents also play a crucial role. The findings’ clinical, societal, research, and policy implications are discussed.